Peran Inklusi Keuangan melalui Integrasi Fintech dalam Stabilitas Sistem Keuangan Indonesia - Rusdianasari, Fitri (Jurnal Ekonomi Kuantitatif Terapan, 2018)
Financial inclusion is a banking instrument that plays an important role in financial system stability through access and financial services. To improve financial performance, technology integration is now an interesting issue. This study aims to determine the role of fintech (financial technology) and other financial inclusion instruments such as MSME credit in influencing the stability of the Indonesian financial system. Error Correction Model (ECM) estimation is used to determine the long and short term effects through cointegration values ??between independent variables in influencing the dependent variable. The results of the analysis show that the number of bank branches has a significant long-term influence on financial stability through NPL performance, so direct investment directed at the banking sector also has a significant influence on financial system stability in the long run. However, fintech instruments such as ATMs and e-money have no significant effect on financial system stability. This condition was motivated by the limited reach of fintech development in the financial sector, especially for the unbankable community